BEWARE ASIAN SERVERS: RACIALIZED PERCEPTIONS OF CHEATING AND SKILL AMONG VIDEO GAME PLAYERS - Tomlinson, Christine; Srauy, Sam (AoIR Selected Papers of Internet Research, 2021)
The resurgent interest in cyberpunk in video game cultures centers the genre's historical and racially problematic themes. Moreover, competitive/online play and the attending toxicity, along with recent Covid-19 based anti-Asian sentiments center the need to theorize the discursive patterns in which these phenomena appear. Taking the recurring talk on various video game forums of isolating Asian servers because "Asians cheat" as a site of inquiry, this project argues that the sentiment of isolating Asian players to region locked servers relies on three entangled discourses: the on-again, off-again collapsing of various Asian identities to a monolithic Pan-Asia (Duara, 2001), Korean and Japanese "expertise" through acquired skill viz. their assumed video game "obsessiveness" (Groen, 2013), and the cheating technological Other seeking to supplant Whiteness at the privileged center of video games (see Nakamura, 2002, 2009). By highlighting these discourses and how they function, this project hopes to lend theoretical nuance to understanding racism in contemporary video game cultures.